Designing and promotion of benefit-sharing mechanisms (BSMs) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Part of a larger project funded by the Challenge Program on Water and Food (CPWF), the BSM is a collective action process where an agreement among watershed inhabitants and stakeholders aims to solve the existing problems in the region such as deforestation, erosion, pollution of water bodies, reduced flow, loss of biodiversity and soil fertility. It seeks the satisfaction of both collective and individual interests without prejudicing the baseline resources, quality of life and well-being of the affected population. The project is developed for three Andean countries: Bolivia (EL Alto, La Paz), Colombia (Coello, Combeima, Alto Putumayo) and Peru (Santa). The project seeks to identify the variables that need to be taken into account when BSMs are designed as means to fight against rural poverty and environmental degradation. In this sense, the Citizen Action Discussion Group (Conversatorio de Acción Ciudadana) serves as a community tool for effective participation and influence on decision-making, linking rights and duties of citizens with conflicts that affect this group.